Understanding the effect of boundary spanning activities on team identification in new product development teams - Pilar Carbonell; Ana I. Rodriguez Escudero (BRQ Business Research Quarterly, 2025)
Despite the relevance of team boundary spanning in new product development (NPD), there is great deal we still do not know about these activities. For example, little is known about how these activities affect the development of team identification, an important emergent state with critical implications for new product performance. This study extends our understanding of this topic by exploring the relationship between team boundary spanning and team identification. This relationship is examined via the intervening mechanisms of team potency and team boundedness and the moderating effect of intra-team communication. Data from a time-lagged survey study of 140 NPD projects revealed that team potency and team boundedness, respectively, positively and negatively mediate the relationship between team boundary spanning and team identification. Intra-team communication was found to reduce the negative effect of team boundary spanning on team boundedness.
Keywords: 031; 032; 036; 650; Team boundary spanning; team potency; team boundedness; team identification; new product performance